2021
DOI: 10.1080/23251042.2021.1973656
|View full text |Cite
|
Sign up to set email alerts
|

‘Scientists don’t care about truth anymore’: the climate crisis and rejection of science in Canada’s oil country

Abstract: Recent research in the area of science and technology studies focuses on climate change denial, the spread of misinformation, and public distrust in climate scientists; these beliefs are held especially by those dependent on fossil fuel extraction for their livelihoods. Many of the same individuals who deny the scientific consensus on climate change are nevertheless directly impacted by the climate crisis and environmental disasters. In fossil fuel dependent locations, do people continue to deny the scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 84 publications
0
7
1
Order By: Relevance
“…Hence, they think that science itself is good, however, the "mainstream" scientists are permeated by false interests. The findings are, however, opposed to interview studies that investigated the arguments of persons who reject the climate change and who reject that lead contaminated soil in their neighborhood is detrimental (Haney, 2022;Messer et al, 2017;Sarathchandra & Haltinner, 2020). In these studies, participants most frequently expressed mistrust and doubts towards scientists' motives, the applied methods, and the presented data (which is very similar to factor 1).…”
Section: General Science Skepticism: Factor Structurecontrasting
confidence: 64%
See 3 more Smart Citations
“…Hence, they think that science itself is good, however, the "mainstream" scientists are permeated by false interests. The findings are, however, opposed to interview studies that investigated the arguments of persons who reject the climate change and who reject that lead contaminated soil in their neighborhood is detrimental (Haney, 2022;Messer et al, 2017;Sarathchandra & Haltinner, 2020). In these studies, participants most frequently expressed mistrust and doubts towards scientists' motives, the applied methods, and the presented data (which is very similar to factor 1).…”
Section: General Science Skepticism: Factor Structurecontrasting
confidence: 64%
“…Because many studies have investigated positive orientations towards science (i.e., trust in science) while largely ignoring negative aspects like distrust in science (Reif & Guenther, 2022), it is essential to also examine general negative beliefs about science. Some previous studies have found that some people who reject specific scientific facts often voice doubt and mistrust towards scientists, their used methods and data, their motives, as well as independence from other interest groups (Haney, 2022;Messer et al, 2017;Sarathchandra & Haltinner, 2020). Therefore, we argue that some persons may have developed a dysfunctional and destructive skepticism towards science and scientists (see also Bauer, 2006;Lewandowsky et al, 2013;Schmid & Betsch, 2019) that might contribute to a broad rejection of scientific claims.…”
Section: General Science Skepticism: Development and Validation Of A ...mentioning
confidence: 68%
See 2 more Smart Citations
“…This may well be a key antidote to conspiracy theories. We know that those working in Alberta's oil fields (the Texas of Canada), like in rural places in the US, are more likely to deny climate change (Haney, 2022), despite being more likely to have witnessed the effects of it first hand, through major floods and forest fires. When the acceptance of climate change is seen as an obligation to profess some kind of allegiance to science over religion or to self-flagellation over having fun, or as the necessary rejection of our friends and family, we all lose.…”
Section: Learning Out Of Climate Change Denial: Learning To Live Toge...mentioning
confidence: 99%